Cooperativity leads to temporally-correlated fluctuations in the bacteriophage lambda genetic switch - Shenker, Jacob Q.; Lin, Milo M. (Frontiers in Plant Science, 2015)
Cooperative interactions are widespread in biochemical networks, providing the nonlinear response that underlies behavior such as ultrasensitivity and robust switching. We introduce a temporal correlation function—the conditional activity—to study the behavior of these phenomena. Applying it to the bistable genetic switch in bacteriophage lambda, we ﬁnd that cooperative binding between binding sites on the prophage DNA lead to non-Markovian behavior, as quantiﬁed by the conditional activity. Previously, the conditional activity has been used to predict allosteric pathways in proteins; here, we show that it identiﬁes the rare unbinding events which underlie induction from lysogeny to lysis.